Effect of lead zinc mineralization area on heavy metals accumulation and geochemical fractions of agricultural soils in Southwest China - Zhenglu Yu; Xuexian Li; Pan Wu; Zhiwei Han; Jian Zhu; Manzhi Chen; Zhuo Chen (Scientific Reports)
Abstract Soils developed in karst regions are widely reported to exhibit high geological backgrounds of heavy metals (HMs) globally. However, due to unique geological conditions, there are both mineralized and/or altered areas of polymetallic minerals in karst areas, and whether the HMs concentrations of regional soil are affected by these mineralized and/or altered areas is far from enough attention at present. This study investigated the accumulation and chemical speciation of HMs in soils from typical lead-zinc mineralized zones in karst areas of Southwest China, using random forest (RF) modeling to identify key driving factors. The results indicated significant variability in HMs concentrations. Cr, Ni, and Cu levels were comparable to Guizhou Province’s background values, while Cd, Pb, Zn, As, and Hg exceeded these values by 0.54 to 44.98 times. Notably, the accumulation of Cd, Pb, and Zn was particularly pronounced, with certain samples surpassing the risk control thresholds for agricultural land. Sequential extraction analysis revealed that Cd and Pb is predominantly found in reducible fractions, (40.61% and 36.49%, respectively), indicating strong bioavailability and potential mobility. RF analysis identified TFe₂O₃ and Al₂O₃ as key factors for the accumulation of As, Hg, Cr, Ni and Cu, while MnO and the distance to lead-zinc mineralization points (DL) significantly influenced Cd, Pb, and Zn levels. This study highlights that HMs accumulation is driven by carbonate rock parent materials and Cd, Pb, and Zn levels exacerbated by lead-zinc mineralization, offering a valuable insight for regional HMs management and control. Meanwhile, the research results can provide references for the geochemical accumulation mechanisms and risk management of soil HMs in mineralized areas (belts) worldwide.